2022
DOI: 10.1111/gcb.16297
|View full text |Cite
|
Sign up to set email alerts
|

Processes and mechanisms of coastal woody‐plant mortality

Abstract: Observations of woody plant mortality in coastal ecosystems are globally widespread, but the overarching processes and underlying mechanisms are poorly understood. This knowledge deficiency, combined with rapidly changing water levels, storm surges, atmospheric CO 2 , and vapor pressure deficit, creates large predictive uncertainty regarding how coastal ecosystems will respond to global change. Here, we synthesize the literature on the mechanisms that underlie coastal woody-plant mortality, with the goal of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 252 publications
1
36
0
Order By: Relevance
“…Although terrestrial woody plant communities sequester carbon at lower rates compared with the rapid rates driven by sediment accumulation in coastal ecosystems (Rogers et al ., 2019), they accumulate large amounts of carbon within living woody biomass with slow turnover (Smart et al ., 2020). The combination of large C pools and low salinity tolerance makes upland coastal forests another important PFT to include in simulations of sea level rise (Smith & Kirwan, 2021; McDowell et al ., 2022). The same salinity response function approaches used for salt‐tolerant species could be applied for freshwater and terrestrial forest PFTs, with much lower salinity thresholds (Fig.…”
Section: Vegetation Functional Types and Traitsmentioning
confidence: 99%
“…Although terrestrial woody plant communities sequester carbon at lower rates compared with the rapid rates driven by sediment accumulation in coastal ecosystems (Rogers et al ., 2019), they accumulate large amounts of carbon within living woody biomass with slow turnover (Smart et al ., 2020). The combination of large C pools and low salinity tolerance makes upland coastal forests another important PFT to include in simulations of sea level rise (Smith & Kirwan, 2021; McDowell et al ., 2022). The same salinity response function approaches used for salt‐tolerant species could be applied for freshwater and terrestrial forest PFTs, with much lower salinity thresholds (Fig.…”
Section: Vegetation Functional Types and Traitsmentioning
confidence: 99%
“…Salinity (ppt) at each site are from , 2006). Additionally, loss of turgor and cell volume can impact structural integrity, cellular function and carbon gain, and eventually lead to cell death (Guadagno et al, 2017;Lamacque et al, 2020;Lambers & Oliveira, 2019;McDowell et al, 2022;Nguyen, Meir, Wolfe, et al, 2017;Sapes & Sala, 2021).…”
Section: The Salinity-induced Ws Deficitmentioning
confidence: 99%
“…Indeed, extensive holm oak diebacks have been recently observed following severe drought episodes (Colangelo et al, 2018;Encinas-Valero et al, 2021;Ogaya et al, 2015Ogaya et al, , 2020Pasquini et al, 2023). Therefore, improving our understanding of the mechanisms underlying holm oak decline and mortality is required to predict Q. ilex forest loss and suggest management measures for its conservation (Gentilesca et al, 2017;McDowell et al, 2022). Previous studies have shown that Q. ilex displays an isohydric behaviour under water stress because it tightly controls stomatal conductance, thus preventing leaf dehydration and embolism formation in xylem vessels (David et al, 2007;Limousin et al, 2022;Nardini et al, 2014;Vaz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%